Floating treatment wetland retrofit to improve stormwater pond performance for suspended solids, copper and zinc - Borne, Karine E.; Fassman, Elizabeth A.; Tanner, Chris C. (Ecological engineering, 2013)
► A retention pond retrofit with a floating treatment wetland was monitored. ► A similar conventional retention pond with same inflow was monitored as a control. ► Copper, zinc and total suspended solids event mean concentration were quantified. ► The FTW pond showed higher treatment efficiency especially for particulate pollutants. A field trial study with side-by-side monitoring of two parallel stormwater treatment ponds, one of which contained a floating treatment wetland (FTW), has been carried out to assess the benefit of retrofitting a conventional retention pond with a FTW. Inflow and outflow event mean concentrations (EMCs) were quantified and used to assess the overall pollutant removal efficiency of each system. Findings show that a FTW can significantly improve the runoff water quality and thus reduce the impact on the receiving environment. The present study reveals that a pond retrofit with a FTW would be more efficient than a conventional retention pond, exhibiting a 41% (for total suspended solids – TSS), 40% (for particulate zinc – PZn), 39% (for particulate copper – PCu) and 16% (for dissolved copper – DCu) lower effluent EMC. Physical entrapment of the particulate pollutants into the roots’ biofilm seems be a significant removal pathway, which could be impacted by the inflow volume. Due to higher humic content, lower dissolved oxygen and more neutral water column pH induced by the FTW, there was increased potential for adsorption processes and/or precipitation as insoluble copper sulphides, in addition to the direct Cu uptake by the plants. The dissolved zinc (DZn) inlet EMCs, which already met the Australian and New Zealand Environment Conservation Council (ANZECC) water quality guidelines and could correspond to an irreducible concentration of the system, were too low to differentiate the performance of either pond.